Risk of adverse pregnancy outcomes of late‐ and postterm pregnancies in advanced maternal age: A national cohort study. (5th April 2020) - Kortekaas, Joep C.; Kazemier, Brenda M.; Keulen, Judit K. J.; Bruinsma, Aafke; Mol, Ben W.; Vandenbussche, Frank; Van Dillen, Jeroen; De Miranda, Esteriek
Abstract: Introduction: There is an increase in women delivering ≥35 years of age. We analyzed the association between advanced maternal age and pregnancy outcomes in late‐ and postterm pregnancies. Material and methods: A national cohort study was performed on obstetrical low‐risk women using data from the Netherlands Perinatal Registry from 1999 to 2010. We included women ≥18 years of age with a singleton pregnancy at term. Women with a pregnancy complicated by congenital anomalies, hypertensive disorders or diabetes mellitus were excluded. Composite adverse perinatal outcome was defined as stillbirth, neonatal death, meconium aspiration syndrome, 5‐minute Apgar score <7, neonatal intensive care unit admittance and sepsis. Composite adverse maternal outcome was defined as maternal death, placental abruption and postpartum hemorrhage of >1000 mL. Results: We stratified the women into three age groups: 18‐34 (n = 1 321 366 [reference]); 35‐39 (n = 286 717) and ≥40 (n = 40 909). Composite adverse perinatal outcome occurred in 1.6% in women aged 18‐34, 1.7% in women aged 35‐39 (relative risk [RR] 1.06, 95% confidence interval [95% CI] 1.03‐1.08) and 2.2% in women aged ≥40 (RR 1.38, 95% CI 1.29‐1.47), with 5‐minute Apgar score <7 as the factor contributing most to the outcome. Composite adverse maternal outcome occurred in 4.6% in women aged 18‐34, 5.0% in women aged 35‐39 (RR 1.08, 95% CI 1.06‐1.10) and 5.2% in women aged ≥40 (RR 1.14, 95% CI 1.09‐1.19), with postpartum hemorrhage >1000 mL as the factor contributing most to the outcome. In all age categories, the risk of adverse pregnancy outcomes was higher for nulliparous than for multiparous women. The risk of adverse outcomes increased in both nulliparous and parous women with advancing gestational age. When adjusted for parity, onset of labor and gestational age, advanced maternal age is associated with an increase in both composite adverse perinatal and maternal outcomes. Conclusions: The risk of adverse pregnancy outcome increases with advancing maternal age. Women aged ≥40 have an increased risk of adverse perinatal and maternal outcome when pregnancy goes beyond 41 weeks.